Reflexões sobre o design sustentável no mercado calçadista: estudo de caso da marca Insecta Shoes - ANGÉLICO, Ana Maria Duarte (2017)
After years of intense industrialization and destruction of the environment, it is possible to say that there is a lot to be done in order to solve ecological problems and reverse the planet’s environmental and social situation, even with the intensiﬁcation of environmental movements. In this sense, this study sought to understand the relationship between industry, economy and sustainable development within the footwear market. The main focus of this work is to analyze the application of sustainable design in footwear design, based on the theories of Manzini and Vezzoli (2016) about the practice of sustainability considering the concept of “Life Cycle Design”. Finally, based on these reﬂections, this research presents a case study of the shoe brand Insecta Shoes, which proposes to seek solutions related to the reduction of social and environmental impacts.